1991
DOI: 10.1128/jb.173.2.559-567.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequence, and expression of a lipase gene from Pseudomonas cepacia: lipase production in heterologous hosts requires two Pseudomonas genes

Abstract: The lipA gene encoding an extracellular lipase from Pseudomonas cepacia was cloned and sequenced. Downstream from the lipase gene an open reading frame was identified, and the corresponding gene was named limA. lipA was well expressed only in the presence of limA. limA exerts its effect both in cis and in trans and therefore produces a diffusible gene product, presumably a protein of 344 amino acids. Replacement of the lipA expression signals (promoter, ribosome-binding site, and signal peptide-coding sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 38 publications
2
92
0
1
Order By: Relevance
“…Lipases from I! cepacia [30] and E! glumae [31] belonging to homology group I also contain two Cys residues.…”
Section: Discussionmentioning
confidence: 99%
“…Lipases from I! cepacia [30] and E! glumae [31] belonging to homology group I also contain two Cys residues.…”
Section: Discussionmentioning
confidence: 99%
“…4), including the heptapeptide consensus motif (IGHSHGG) thought to lie at the active site of this family of lipases (Wohlfarth et al, 1992) (data not shown). A hlyC (iviXII)-containing mutant strain of V. cholerae that we constructed, AC-V195 (see below), lost the ability to produce a clearing zone around colonies grown for 48 h on agar media containing emulsified tributyrin (Jorgensen et al, 1991) (Fig. 5), thus demonstrating that the htyC (iviXII) locus is required for this secreted lipase activity.…”
Section: In Vivo-induced Locus Encoding a Secreted Lipasementioning
confidence: 99%
“…Pseudomonas glumae was also found to be efficient in a system of washing model (Iizumi et al, 1991, Jorgesen et al, 1991. Span 80 was chosen for the following studies as it showed the highest percentage of oil removal in the presence of lipase.…”
Section: Resultsmentioning
confidence: 99%